Conceptions of Academic Talent: Implications for talent identification and development - Richards, Zena (South African Journal of Higher Education, 2016)
The terms often used in conceptualisations of academic talent are highly variable, with each term employed holding specific ideological implications. This paper aims to provide a broad overview of the concept of ‘academic talent’ in the international and South African literature. In an attempt to connect international academic discourses to the local context, the review explores several discourses of academic talent within the South African context. It is argued that holistic, student-centred approaches towards nurturing academic talent will allow for contextual considerations in the identification of individuals selected to participate in talent development programmes. It is also argued that inclusive approaches to developing talent appear to be premised on the view that learners from educationally disadvantaged backgrounds can be nurtured towards academic success. Addressing educational disadvantage is not a ‘quick fix’ but requires intensive support and an understanding of issues facing disadvantaged learners (including values orientation conflicts, self-esteem and self-concept). What is pertinent in this paper is that the assumptions and values upon which the constructs are based need to take into account individuals within a particular context. Contextual variability therefore requires reformulations of the construct.